A new species of the genus Anoplistes Audinet-Serville, 1834 (Coleoptera, Cerambycidae, Cerambycinae, Trachyderini) from Mongolia - Karpiński, Lech (Zootaxa, 2020)
Anoplistes kaszabi sp. nov. is described from Mongolia. Distinguishing characters from closely related Anoplistes mongolicus Ganglbauer, 1889 are presented and their ecological dissimilarity is discussed. High-quality stacked photographs of the habitus of the specimens are presented for both species and their geographical distributions are mapped. The new species differs from A. mongolicus mainly by the more elongate pronotum with different sculpture, the more evenly and densely pubescent elytra, the slender body of smaller size in both sexes, as well as by the different shape of female antennomeres. Additionally, they are most likely associated with two different host plants. Moreover, Anoplistes amoenus Reitter, 1898 (stat. res.) is herein restored to specific rank due to its clear distinctness compared to the discussed taxa.